Entrepreneurial Intentions: Entrepreneurship Education Programs, Cognitive Motivational Factors of Planned Behavior, and Business Incubation Centers - Temoor Anjum; Julián Andrés Díaz Tautiva; Muhammad Asif Zaheer; Petra Heidler (MDPI AG, 2024)
Previous studies have explored the factors influencing entrepreneurial intentions (EIs), primarily focusing on personality traits and various psychological aspects. This study, however, investigates external factors, such as entrepreneurship education programs (EEPs), cognitive motivational factors associated with the Theory of Planned Behavior (TPB), and the impact of business incubation centers (BICs), as moderators of EIs. The research involved 458 respondents from diverse higher education institutions in Asia. Our findings indicate that EEPs and BICs at universities positively and significantly affect students' EIs. Additionally, the cognitive factors linked to TPB demonstrate a positive and significant direct effect on EIs while also acting as mediators between EEPs and EIs. These findings underscore the importance of adopting a multilevel perspective in designing and implementing EEPs and BICs to better comprehend the determinants of EIs. Our study provides valuable insights for university administrators, policymakers, and entrepreneurship instructors in developing countries to improve the university entrepreneurial ecosystem by creating cohesive programs and supportive institutions. Moreover, the results can serve as encouragement for individuals embarking on an entrepreneurial journey.